A quality management model for English program curricula in Thai secondary bilingual schools - Suwan, Nanteya; Sisan, Boonchan (Edelweiss Applied Science and Technology, 2025)
This study aimed to develop and validate a quality management model for administering English program curricula in bilingual public schools at the secondary level in Thailand. Using a mixed-methods approach, the model was developed based on a systematic content analysis and synthesis of the relevant literature, documents, and the CIPP (Context-Input-Process-Product) model. The model’s quality was then evaluated by a panel of nine experts through a focus group discussion, considering four dimensions: usefulness, feasibility, appropriateness, and accuracy. Data were analyzed using descriptive statistics. Findings provide a robust model with three core factors of academic quality administration: (1) Input – leadership, strategic planning, systematic processes, human resources; (2) Process – curriculum development, instructional management, assessment, supervision, educational technology, quality assurance, utilizing the PDCA (Plan-Do-Check-Act) cycle; and (3) Output – stakeholder focus, learner quality, knowledge management, and continuous improvement. The experts validated the model, confirming its high quality overall (M = 4.77, SD = 0.29), with usefulness and accuracy being the highest-rated dimensions. The study successfully developed and validated a holistic, systems-based model for academic quality management, providing educational administrators with a practical, evidence-based framework to systematically enhance the quality and effectiveness of English bilingual programs in public secondary schools. This model offers a useful, validated framework for administrators to improve the quality and effectiveness of English bilingual programs systematically.